الاستثمار في المورد البشري و دوره في تحقيق الميزة التنافسية في الادارة الرياضية - حمدي, عبد المنيب (My University, 2020)
الملخص : بالعربية الاستثمار في المورد البشري و دوره في تحسين اداء العاملين لدى الادارة الرياضية أهدف الدراسة:  . معرفة مدى استثمار مديرية الشباب والرياضة للمورد البشري الداخلي والخارجي.  . التعرف على مدى انعكاس هذا الاستثمار على تسيير مخلف مصالحها.  . التعرف على معايير استقطاب المورد البشري التي تنتهجه مديرية الشباب والرياضة في مجال التوظيف.  . تسليط الضوء على السياسة التي تتبناها مديرية الشباب والرياضة في تكوين ورسكلة موردها البشري.  . التعرف على نظام تقييم المورد البشري المعتمد في مديرية الشباب والرياضة .  التساؤل العام: هل للاستثمار في المورد البشري دور في تحسين اداء العاملين لدى الادارة الرياضية ؟  التساؤلات الجزئية:  . هل لاستقطاب المورد البشري معايير مدروسة للتوظيف في الإدارة الرياضية ؟  . هل لتكوين ورسكلة المورد البشري سياسة واضحة لدى الإدارة الرياضية ؟  . هل لنظام تقييم المورد البشري دور يعكس المردود الفعلي للموظفين في الإدارة الرياضية ؟  الفرضية العامة: الاستثمار في المورد البشري له دور في تحسين اداء العاملين لدى الادارة الرياضية.  الفرضيات الجزئية:  . لاستقطاب المورد البشري معايير مدروسة للتوظيف في الادارة الرياضية.  . لتكوين ورسكلة المورد البشري سياسة واضحة لدى الادارة الرياضية.  . لنظام تقييم المورد البشري دور يعكس المردود الفعلي للموظفين في الادارة الرياضية.  عينة الدراسة: المسح الشامل كونها من أبسط طرق اختيار العينات وتتكون عينة بحثنا هذا من 35 موظف بمديرية الشباب والرياضة.  المنهج المستخدم: اعتمدنا في بحثنا على المنهج الوصفي لكونه يتلاءم مع طبيعة المشكلة المدروسة.  أدوات الدراسة: اعتمدنا على استبيان اشتمل على 3محاور تكون كل محور من 10 عبارات. كلمات المفاتيح: الاستثمار في المورد البشري الميزة التنافسية الادارة الرياضية بالفرنسية Mots clés: بالإنجليزية Keywords: جاء هذا البحث في فصول . الفصل الأول: تناولنا به الخلفية النظرية و الدراسات السابقة وتناول الفصل الثاني: الاطار العام للدراسة أما الفصل الثالث: الاجراءات الميدانية للدراسة الفصل الرابع : عرض و مناقشة النتائج الفصل الخامس: استنتاجات و اقتراحات من أهم النتائج التي توصل إليها الباحث : توصل الباحث للعديد من التوصيات أهمها :  اهتمام مديرية الشباب والرياضة بالمورد البشري غير كافي ولا يرتقي إلى المستوى المطلوب  . أكدت الدراسة أن هناك تأثير مباشر وبصورة جيدة لتخطيط وتطوير طرق استقطاب المورد البشري  . أكدت الدراسة أن التدريب والبرامج التدريبية المتبعة في المديرية تعمل على رفع كفاءة الموظفين إلا أنها ليست على المستوى المطلوب  . أكدت الدراسة على أن عملية التقييم المتبعة في المديرية تعمل على رفع مستوى أداء العاملين واستثمار قدراتهم بما يساعدهم على التقدم والتطور ولكن بشكل ضعيف توصل(ت) الباحث لمقترحات عديدة أهمها : أهم المقترحات  . الاهتمام بإدارة الموارد البشرية كونها تواكب التطور وتعمل جاهدة على تنشيط حوافز التغيير وتنمية عوامله وتحريك متطلباته.  . فتح تخصصات في إدارة الموارد البشرية في المعاهد الرياضية.  . تكوين إطارات متخصصة في إدارة الموارد البشرية على أيدي ذات خبرة وكفاءة متخصصة في هذا المجال.  . ضرورة أن تنظر الادارة الرياضية إلى الاستثمار في المورد البشري باعتباره أحد المداخل الإستراتيجية لزيادة الكفاءة والفعالية التنظيمية. كشاف بالفرنسية Faculté : staps Département : administration N° d’ordre : N° d’inscription : M201535091824 Chercheur : hamdi abdelmounib Soutenu publiquement le :24/06/2020 Titre de la thèse (mémoire) : -Investing in human resources and its role in achieving competitive advantage in sports management. Language de la thése :anglais Modèle de la thése : master Pays : RÉPUBLIQUE ALGÉRIENNE-M’SILA Université : Université de M’sila Nom et Prénom de l’encadreur : tebani ali Grade : Nombre de page : 119 pages (cd-Rom* word * PDF) Ficher électronique Spécialité : administrationn Option : Résumé : The objectives of the study are * Find out the extent to which the Directorate of Youth and Sports invests in the internal and external human resource. *Find out how this investment reflects on the competitive advantage of sports management. *To identify the criteria for attracting human resources from the Directorate of Youth and Sports *Highlighting the policy adopted by the Directorate of Youth and Sports in the formation and reining of its human resource. *Know the role of training and incentive investment in human resources in achieving competitive advantage in sports management. The general question *Does investing in human resources play a role in achieving competitive advantage in sports management? Partial questions *Is there a role for training and incentive investment of human resources in achieving competitive advantage in sports management? Is investing in human resources reflected in competitive advantage?* *Does attracting human resources have well-thought-out criteria for achieving competitive advantage in sports management? General hypothesis: Investing in human resources has a role to play in achieving competitive advantage in sports management. Partial hypotheses: *There is a role for training and incentive hr investment in achieving competitive advantage in sports management. *To attract human resources are well-thought-out standards in order to achieve competitive advantage in sports management. Investment in human resources is reflected in competitive advantage. Mots clés : human resources investing in human resources الكلمات المفتاحية: Abstract Key words : Ce mémoire et contienne de trois « 03 » chapitre Chapitre 1: Chapitre 2 : Chapitre 3 : Chapitre 4 : Chapitre 5 : Résultat essentielle que le chercheure à conclue : The most important findings: The interest of the Directorate of Youth and Sports in investing in the human resource is insufficient and does not rise to the required level. *The study confirmed that there are direct and good programs to plan and develop ways to attract human resources. *The study confirmed that the training and training programs followed in the directorate work to raise the efficiency of the employees but it is not at the required level. *The study confirmed that the evaluation process followed in the directorate works to raise the level of performance of employees and invest their abilities to help them progress and develop but weakly. *The study confirmed that attracting and stimulating human resources in the Directorate of Youth and Sports is slowly taking place. *The study confirmed that to achieve competitive advantage in sports management must invest fully in the human resource. *The study confirmed that the stimulation of the human resource positively affects the achievement of competitive advantage. The most important suggestions: *Attention to human resources management as it keeps pace with development and works hard to activate the incentives for change and develop its factors and move its requirements. Opening specialties in human resources management in sports institutes.* *Creating specialized frameworks in human resources management by experienced and competent specialists in this field. *Sports management should view investment in human resource as one of the strategic approaches to increasing efficiency and organizational effectiveness.
Keywords: الاستثمار في المورد البشري; الميزة التنافسية; الادارة الرياضية